Small Cell Neuroendocrine Carcinoma Masquerading as Cellulitis and Causing Blindness via Bilateral Orbital Involvement. (June 2013) - Atik, Alp; Krilis, Matthew; Shannon, Kerwin
ABSTRACT Case report: We report the first case of small cell neuroendocrine carcinoma involving both orbits and causing complete blindness. The patient was initially prescribed antibiotics for right periorbital cellulitis, but magnetic resonance imaging demonstrated abnormal enhancing tissue in the superomedial and superior right orbit with destruction of the anterior lamina papyracea, extension into the anterior ethmoid air cells, further extension into the right frontal bone and pockets of fluid in the right frontal lobe. Histopathology from the orbital tissue and right frontal subdural empyema demonstrated small cell neuroendocrine carcinoma of 'small blue cell' subtype. The patient received multidisciplinary treatment combining surgery, chemotherapy (both systemic and intra-arterial) and radiotherapy but passed away in the second year of treatment. Comment: Primary small cell neuroendocrine carcinoma is an extremely rare tumour, most frequently occurring in the lungs. An understanding of the pathology has been difficult, due to its rarity and the complexity of the histological diagnosis. Neuroendocrine carcinoma has a very poor prognosis and further research is required for more effective treatment options.